Under Caesar's sword : how Christians respond to persecution / edited by Daniel Philpott, University of Notre Dame, Timothy Samuel Shah, Baylor University and Georgetown University. - Philpott, Daniel, 1967-; Shah, Timothy Samuel (Law and Christianity., 2018)
The global persecution of Christians is an urgent human rights issue that remains underreported. This volume presents the results of the first systematic global investigation into how Christians respond to persecution. World-class scholars of global Christianity present first-hand research from most of the sites of the harshest persecution as well as the West and Latin America. Their findings make clear the nature of persecution, the reasons for it, Christian responses to it - both non-violent and confrontational - and the effects of these responses. Motivating the volume is the hope that this knowledge will empower all who would exercise solidarity with the world's persecuted Christians and will offer the victims strategies for a more effective response. This book is written for anyone concerned about the persecution of Christians or more generally about the human right of religious freedom, including scholars, activists, political and religious leaders, and those who work for international organizations.